Clinicopathological investigation of the background of cognitive decline in elderly schizophrenia. Issue 2 (4th April 2021) - Miwa, Ayako; Hirano, Mitsuaki; Torii, Youta; Sekiguchi, Hirotaka; Habuchi, Chikako; Fujishiro, Hiroshige; Yoshida, Mari; Iwai, Kiyoshi; Kawashima, Kunihiro; Iritani, Shuji
Abstract: Objective: We have often observed dementia symptoms or severe neurocognitive decline in the long-term course of schizophrenia. While there are epidemiological reports that patients with schizophrenia are at an increased risk of developing dementia, there are also neuropathological reports that the prevalence of Alzheimer's disease (AD) in schizophrenia is similar to that in normal controls. It is difficult to distinguish, based solely on the clinical symptoms, whether the remarkable dementia symptoms and cognitive decline seen in elderly schizophrenia are due to the course of the disease itself or a concomitant neurocognitive disease. Neuropathological observation is needed for discrimination. Methods: We conducted a neuropathological search on three cases of schizophrenia that developed cognitive decline or dementia symptoms after a long illness course of schizophrenia. The clinical symptoms of total disease course were confirmed retrospectively in the medical record. We have evaluated neuropathological diagnosis based on not only Hematoxylin–Eosin and Klüver–Barrera staining specimens but also immunohistochemical stained specimens including tau, β-amyloid, pTDP-43 and α-synuclein protein throughout clinicopathological conference with multiple neuropathologists and psychiatrists. Results: The three cases showed no significant pathological findings or preclinical degenerative findings, and poor findings consistent with symptoms of dementia were noted. Conclusion: Although the biological background of dementia symptoms in elderly schizophrenic patients is still unclear, regarding the brain capacity/cognitive reserve ability, preclinical neurodegeneration changes in combination with certain brain vulnerabilities due to schizophrenia itself are thought to induce dementia syndrome and severe cognitive decline.